Programa de mejora del nivel de concientización ciudadana sobre la recolección de residuos sólidos en el barrio de San Carlos, Huancayo - Limache Flores, Marisol (2022)
The problems of solid waste collection in the San Carlos neighborhood not only generate a bad aesthetic, but also public health problems, as well as being a waste of economic opportunity for all the residents of the neighborhood. This research seeks to raise public awareness about solid waste collection, for which a work program was carried out which includes training, advertising, leaflets and poles related to solid waste collection. With the thesis developed, it was possible for people to learn about solid waste segregation, recycling, landfills, the role of municipalities, prevention, health, hygiene and safety. Among the most outstanding results we have that the training and sensitization work was favorable in raising awareness about the recycling of people, obtaining knowledge on issues of segregation and adequate collection of solid waste in favor of the environment.